A NUCLEAR MEMBRANE CHANGE AFTER PARTIAL HEPATECTOMY - Kishimoto, Susumu (The Rockefeller University Press, 1964)
Partial hepatectomy (67 per cent extirpation) of the rat leads to a change in the membrane of liver nuclei (purified with citric acid) detectable as an increase in electrophoretic mobility. No change is detectable 2 hours after the operation, but between 2 and 6 hours about a 1.4-fold increase in mobility occurs after which the mobility becomes constant at the elevated level. Removal of only 10 per cent of the liver causes no detectable change in 6 hours. Bilateral adrenalectomy immediately before partial hepatectomy does not affect the development of the nuclear change. Actinomycin D and p-fluorophenylalanine, but not noradrenalin, ionizing radiation, or EDTA, suppress the increase in electrophoretic mobility. The level of actinomycin D required to block the nuclear membrane change is 6 times greater than that necessary to prevent the rate increase in hepatic RNA metabolism that follows removal of part of the liver. This discrepancy and the difference in the response to noradrenalin indicate that, at least initially, the nuclear membrane change and the change in the rate of RNA synthesis are independent processes. The inability of EDTA to block the nuclear membrane change shows that the Zn(++) requirement for DNA replication is not related to the events that lead to the alteration in the electrokinetic properties of liver nuclei.